Determinants of tobacco use transitions in smoker nursing students in Catalonia: A prospective longitudinal study - Kenza Laroussy; Esteve Fernández; Yolanda Castellano; Marcela Fu; Antoni Baena; Ariadna Feliu; Armando Peruga; Mercè Margalef; Olena Tigova; Jordi Galimany; Montserrat Puig; Carmen Moreno; et al. (Tobacco Induced Diseases)
Introduction The use of emerging tobacco and nicotine products affects tobacco use behaviors among college students. Thus, we aimed to examine transitions in tobacco use patterns and identify their predictors among smokers in a cohort of nursing students in Catalonia (Spain).